Correlation between crystallographic texture and the degree of L1(0)-ordering in post-annealed Ag/CoPt bilayers and comparison with Ag/CoPt nanocomposites - Manios, E.; Stamopoulos, D.; Panagiotopoulos, I.; Niarchos, D. (INTERNATIONAL CONFERENCE ON SUPERCONDUCTIVITY AND MAGNETISM (ICSM), 2009)
CoPt and FePt compound films with L1(0) ordered structure have been intensively studied,due to their extremely high uniaxial magnetocrystalline anisotropy which makes them suitable for application in ultra high density magnetic recording media. A basic requirement in these type of media is the development of strong perpendicular magnetic anisotropy. The role of Ag underlayers in promoting strong (001) crystallographic texture and perpendicular magnetic anisotropy in post-annealed Ag/CoPt and Ag/FePt bilayers (BLs) has already been reported, along with a possible correlation between L1(0) formation and development of (001) crystallographic texture. In this work we present new data, which provide further evidence that there is indeed such a correlation during the annealing process of Ag/CoPt BLs. The most obvious manifestation of this correlation is the fact that the X-ray intensity ratios I-001/I-002 (used as a measure of the degree of L1(0)-ordering) and I-002/I-111 (used as a measure of the crystallographic texture) and the coercivity H-c and relative remnant magnetization m(r) (for field H normal to the surface of the films) exhibit the same kind of dependence from the thickness of the Ag underlayer. Comparison with respective crystallographic data from post-annealed Ag/CoPt nanocomposites (NCs) shows that in the case of NCs the (001) texture starts to degrade for lower total film thickness, compared to the case of BLs. This difference can be attributed to the structural incoherence in the growth of the CoPt grains imposed by the presence of Ag inside the Ag/CoPt NCs, while in BLs Ag is only used as an underlayer. Based on the above data and on detailed Heavy Ion Elastic Rutherford Back Scattering (HIRBS) measurements, performed on post-annealed Ag/CoPt NCs, we propose a possible mechanism for the interpretation of the observed correlation. The proposed mechanism is based on the reduction of total strain (residual strain of as-deposited film and transformation strain due to deformation of the unit cell as L1(0)-CoPt is formed) throughout the annealing process.